Synthesis of Bisflavanol-Type Natural Products and Their Analogues via Self-Coupling of C8-Methylol Catechin Derivatives - Huang, Deng-Ming; Li, Hui-Jing; Zhao, Yan; Wu, Yan-Chao (Synthesis, 2019)
A highly efficient and regioselective self-coupling of C8-methylol catechin derivatives is developed for the synthesis of dimeric flavanol analogues under metal-free and mild conditions. Its applicability is showcased by the efficient synthesis of bisflavanol-type natural products bis-8,8′-catechinylmethane, bis-8,8′-epicatechinylmethane, talienbisflavan A, and oolonghomobisflavan A. The novel self-coupling mechanism sheds new light on the classical Friedel–Crafts alkylation mechanism in acid-catalyzed catechin–formaldehyde condensation.
Keywords: bis-flavanol; catechin; self-coupling; metal-free; regioselective